The Role of the Peoples of the Uralic Language Family in the Formation and Development of the Russian Civilization - Nina N. Loginova; Marko D. Petrović; Irina A. Semina; Yuriy P. Shabaev; Nataliya V Yakovenko (Indonesian Journal of Geography, 2021)
The study examines the territorial organization of the Ural peoples and languages, reveals the features of the regional interaction and population dynamics, addresses the problems of the ancestral homeland and ethno genesis, the role of Finno-Ugrians in the history of Russia, highlights the acute issues of preserving languages and culture. The research focuses on some features in the development of the Uralic ethnic groups within the framework of the Russian civilization. It is alleged that the ethnic and political consolidation of most Finno-Ugric tribes was born in the bowels of the ancient Russian state and the first sprouts of the future unity of peoples were born, and their role in the powerful national-state construction that unfolded on the huge Eurasian territory of Russia in the period between 16th and 20th century is analyzed. The outcomes confirm that the Finno-Ugric peoples have always been an organic part of the Russian ethno-cultural mosaic. They actively participated in the strengthening of the state, mastered its vast natural wealth, and created the economic power of the country. Due to the fact that in Finno-Ugric, significant attention is paid to the problems of preserving languages and culture among Samoyed peoples, which cannot be called Finno-Ugric, we propose to use the term "Uralistics" more widely. This is a more accurate concept and can be used in the study of cultural processes among the peoples united in the Uralic language family.